"How" vs. "Why" questions in symbiogenesis, and the causal role of synergy. (July 2021) - Corning, Peter A.
Abstract: Mutualistic symbiosis, we now know, is a ubiquitous phenomenon in the natural world. And, in every case, there was an initial "genesis" – a "how" process that may have been at once unique to each situation and perhaps also shared a common set of facilitators. However, a full explanation of symbiogenesis also requires an answer to the "why" question, for natural selection is a stringent economizer. Something as contrarian as mutualistic cooperation between "differently named" organisms must also provide functional advantages for the participants that will be favored by natural selection (differential survival and reproduction). Enter the "Synergism Hypothesis" – the thesis that synergistic functional effects of various kinds are a common cause of cooperative relationships of all kinds in nature, including symbioses. When different organisms have complementary capabilities that are mutually beneficial and cannot otherwise be attained, the benefits derived from symbiotic cooperation will outweigh the costs. Among the many documented cases of symbiogenesis over time, lichens provide perhaps the most familiar, well-studied example, while the eukaryotes are often cited as a game-changer. The answer to the "why" question was, in each case, determinative for symbiogenesis. Highlights: "Why" questions refer to the functional/selective advantage(s) of a trait. Natural selection is a stringent economizer. Symbiosis produces otherwise unattainable functional synergies. Symbiogenesis depends upon these functional advantages. Lichens and eukaryotic protists provide well-studied examples.